Entangling Economics of Fishing to the Sustainability of Coastal Households of Indian Ocean - Adili Yohana Zella; Antonia Mpemba (Current Aspects in Business, Economics and Finance Vol. 6, 2022)
Fisheries and aquaculture are socio-economic activities that employ millions of people around the world as a source of income and livelihoods. However there are uncertainties in this sector which alter attainment of sustainability of coastal households. This study assesses the determinants influencing fishing income of households living in coastal areas of Indian Ocean by using Mafia District, Tanzania as a study case. Data collected by using survey and participatory rural appraisal (PRA) to 120 randomly households. Collected data were analysed both statistically and contently. The result revealed that, there are several economic activities conducted in the study area, where 41.47% of the households indicated that fishing is the major economic activity for their livelihood with average income per day of 24.41 USD (51 250 TZS); whereas, fish related activities contributes 7.14 USD (15 000 TZS) and other economic activities wealth 2.38 USD (5000 TZS) per day. The paper concludes that fishing contributes higher household’s income compare to other activities. The paper recommends the government or other stakeholders to provide credit or subsides in improved fishing gears so as to acquire sustainability.